Efficient neural encoding as revealed by bilingualism - Charlotte Moore; Peter W. Donhauser; Denise Klein; Krista Byers-Heinlein (Proceedings of the National Academy of Sciences, 2025)
The remarkable human capacity for bilingual and multilingual acquisition raises fundamental questions about how the brain develops efficient systems for processing multiple languages. In this study, we used neural network models trained on natural speech input to examine how these efficient representations emerge. Our models show that multiple phonological systems can be organized through parallel representations, preserving the unique aspects of each language while maintaining shared articulatory features. This parallel structure scaled effectively from two to three languages without needing additional neural architecture, highlighting the inherent efficiency in multilingual processing. Furthermore, the development of phonological representations varied based on the timing of language exposure, showing how earlier-learned languages shape the acquisition of subsequent ones. These findings imply that the human ability to speak multiple languages may arise from general principles of neural organization that optimize shared resources while maintaining essential distinctions between languages. This work has important implications for language learning, brain plasticity, and cognitive development.